Japanese nationwide surveillance in 2011 of antibacterial susceptibility patterns of clinical isolates from complicated urinary tract infection cases. Issue 9 (September 2015) - Ishikawa, Kiyohito; Hamasuna, Ryoichi; Uehara, Shinya; Yasuda, Mitsuru; Yamamoto, Shingo; Hayami, Hiroshi; Takahashi, Satoshi; Matsumoto, Tetsuro; Minamitani, Shinichi; Kadota, Jun-ichi; Iwata, Satoshi; Kaku, Mitsuo; et al.
Abstract To investigate antimicrobial susceptibility patterns of various bacterial pathogens isolated from complicated urinary tract infection (UTI) cases, the Japanese Society of Chemotherapy, the Japanese Association of Infectious Disease, and the Japanese Society of Clinical Microbiology conducted the second nationwide surveillance from January to September 2011. With the cooperation of 42 medical institutions throughout Japan, 1036 strains belonging to 8 clinically relevant bacterial species were collected. Among methicillin-resistant Staphylococcus aureus (MRSA) strain, the vancomycin (VCM) MIC for 5.5% (3/55) of the strains was 2 μg/mL. Ampicillin, VCM, and linezolid were relatively active against 209 Enterococcus faecalis strains. The proportion of fluoroquinolone (FQ)-resistant strains was >20%. The MIC90 of FQs against the 382 Escherichia coli strains was 2–64 mg/L and the proportion resistant to FQs was approximately 30%. However, susceptibility of E. coli to sitafloxacin was still high (MIC90 = 2 mg/L). Fifty-eight (15.2%) of 382 E. coli, 6 (4.5%) of 132 Klebsiella pneumoniae, 1 (2.4%) of 41 Klebsiella oxytoca and 4 (6.8%) of 59 Proteus mirabilis strains were suspected of producing extended-spectrum beta-lactamase. Of 93 Pseudomonas aeruginosa strains, the proportions resistant to imipenem, amikacin, and ciprofloxacin were 21.5%, 4.3%, and 20.4%, respectively. Four strains (4.3%) were found to be multidrug-resistant. In complicated UTI cases, all of MRSA and E. faecalis were susceptible to all anti-MRSA agents. Sitafloxacin was active against other FQ-resistant E. coli strains. The isolation of extended-spectrum beta-lactamase-producing and multidrug-resistant strains increased.